Management of Migratory Exchange Taking into Account Features of Standard Regulation of Recognition / Validation and an Assessment of Qualifications Within the CIS Countries, EEU and BRICS - L. A. Sokolova; I. I. Sokolov; F. T. Prokopov (Управление)
Legal regulation of national qualifications systems in countries-participants of the CIS, EAEU and the BRICS and the prospects for cooperation in the field of free labor-force movement within these unions, connect with the solution of problems of mutual recognition of occupation qualifications, their level of qualifications and methods of assessment within the subjects of migration transfer processes.